Estimating Consumer fs Response to Livestock Products Food Quality: Evidence from Households in Indonesia - Muzayyanah, Mujtahidah Anggriani Ummul (2016)
We estimated qualityelasticity of livestock products foods consumption with respect to income over time. Household expenditure survey data were used in this study particularly household. Based on Engel’s framework, the basic analysis is used to analyze the expenditureand quantity onlivestock products food demand. The result showed that income affected the expenditure and quantity demand of beef, chicken, egg, and milk. Estimation of expenditure, quantity, and quality elasticity showed that elasticities of these foods respecttohousehold income. Change of income and price is responsive to these food items. Thus, improve the quality of food consumption, particularly for high-value food e.g. animal protein food is important agenda.